GENDER STRUGGLE OF MAIN CHARACTER IN EDITH WHARTHON’S THE HOUSE OF MIRTH NOVEL - Fergie Eka Wahyu Nusantara; Nasrullah Nasrullah; Jonathan Irene Sartika Dewi Max (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
Feminism examines every gender gap, from identity, discrimination, and exploitation. One of the focuses in the study of gender identity is gender struggle and being present in novels. This research discusses the gender struggle for female characters, namely Lily Bart in Edith Wharton's novel The House of Mirth. The purpose of this study is to identify the existence of gender struggles experienced by the character of Lily Bart and describe the development of characters in these struggles. This research uses qualitative research methodology and gender struggle studies. Furthermore, the theory used in gender struggle includes several experts (Paddy McQueen, Bell Hooks, several other experts) and Jonathan Webber's theory of character development. In this case, the forms of struggle are characterized in character development analysis which seeks to find changes in the character of Lily Bart and its correlation to her struggle. The development of the character of Lily Bart is described in three phases. In the initial phase introduces the main objectives, the second phase changes due to conflict and challenges, and the third phase becomes the result of character change. The results showed that the character of Lily Bart as the main character in the novel shows a gender struggle. The forms of gender struggle that are experienced include facts of life, dream, love and affection. In this case, the forms of struggle are characterized in character development analysis which seeks to find changes in the character of Lily Bart and its correlation to her struggle.